Identification of genes with greater mRNA content in 17.5-day than 15.5-day bovine embryos - Glover, Michelle D., author; Seidel, George, Jr., advisor; Niswender, Gordon, committee member; Blair, Carol D., committee member; Bowen, R. A., committee member; Clay, Colin, committee member (Colorado State University. Libraries, 1999)
Considerable embryonic loss occurs between days 15 and 18 of gestation in cattle (estrus=day 0), when several critical cellular and molecular events occur. To gain insight into these events, the mRNA differential display technique was used to identify transcripts present in greater abundance in 17.5-day compared to 15.5-day bovine embryos. Eight unique cDNA fragments were identified. Four of the eight candidate clones were confirmed by Northern blot analysis to be up-regulated between days 15.5 and 17.5 of pregnancy. These four cDNA fragments were subcloned and sequenced. It was revealed that nucleotide sequences for three genes had known homologs; one cDNA fragment was homologous to human and rat allograft inflammatory factor-1 (AIF-1), the second was homologous to human LERK-5 cDNA, and the third gene was bovine IFN-T. One cDNA fragment did not match sequence identities to previously reported genes. A gene fragment encoding bovine AIF-1 and the unidentified gene were selected for the following studies. To determine if elevated gene expression continues beyond day 17.5 of pregnancy, Northern blot analysis was conducted using total RNA isolated from five embryos collected from days 17.5 to 36 of gestation. In addition, Northern blot analysis was used to determine whether these genes were expressed in several adult bovine tissues. The mRNA encoding AIF-1 was present in developing placenta through day 36 of gestation, and abundant levels were observed in adult bovine spleen and lung. The novel cDNA fragment hybridized only to total RNA isolated from 17.5-day embryos; hybridization of the probe was not evident in adult tissues. A cDNA library constructed from 25-day bovine embryos was used to isolate additional nucleotide sequence for bovine AIF-1 and the novel cDNA fragment. The cDNA clone encoding AIF-1 had 88% and 84% sequence identity to human and rat AIF-1; its open reading frame encoded a protein that was 82% and 78% homologous to the amino acid sequences for human and rat AIF-1. Additional sequence information obtained for the novel cDNA fragment was not homologous to previously reported genes.
Keywords: anatomy and physiology; animals; genetics; molecular biology; livestock